Enhancing SWIPT systems: a systematic review of rectifier technologies, efficiency, and integration strategies - Khalaf, Qasim M.; Sali, Aduwati; Ismail, Alyani; Ahmad, Mohd Yazed; Soubhi Hussein, Yaseein; Ali Shah, Jawad (Institute of Electrical and Electronics Engineers Inc., 2025)
This paper reviews the recent advances in rectifier technology for simultaneous wireless information and power transmission (SWIPT) systems in a systematic way, focused on ways to make them more efficient, scalable, and easier to integrate. It analyzes the outcomes of innovative experiments employing standard techniques to enhance energy harvesting (EH) and data transmission in SWIPT by tackling issues related to size reduction, multi-band functionality, and environmental sustainability. It also examines alternative design methodologies, including metamaterials and sophisticated rectenna designs, capable of attaining higher power conversion efficiencies while minimizing their dimensions. The SWIPT architecture utilized by artificial intelligence (AI)- and Deep Reinforcement Learning (DRL) optimization enhances the performance of SWIPT systems by increasing the reliability of RF-to-dc conversion and communication across varying channel conditions. The results show that flexible and wearable rectifier technologies, when combined with antenna co-design and advanced power management circuits, could enable truly self-powered IoT systems. Such devices would be capable of supporting applications in healthcare monitoring, smart textiles, and industrial sensing, continuous operation without batteries, while also reducing maintenance costs and electronic waste. Finally, we emphasize sustainability and interdisciplinary perspectives, recommending life-cycle assessments to address environmental impact and collaborative approaches that unite circuit, antenna, and protocol design. These reflections identify both the opportunities and bottlenecks that must be addressed for SWIPT rectifiers to enable practical 5G, 6G, and beyond applications.